Artificial Intelligence in Education Management: A Bibliometric Mapping of the Intellectual Structure and Emerging Research Themes - Winalda Adelia (International Journal of Educational Administration, Management, and Leadership, 2025)
This study explores the intellectual structure and emerging research trends of artificial intelligence in education management. It identifies six major research streams: (1) ai-driven educational governance, data-centric decision making, and digital transformation, (2) machine learning-based decision support systems and predictive analytics in education management, (3) data-driven educational intelligence and learning analytics in higher education, (4) ai-enabled educational leadership and sustainable development, (5) institutional effectiveness and ai-supported management systems, and (6) foundational education management as the core conceptual domain. co-word analysis further reveals emerging thematic patterns such as artificial intelligence applications, decision-making systems, machine learning, learning analytics, digital transformation, and information management in educational contexts. in terms of methodology, this study employs a bibliometric approach using data from 91 journal articles indexed in Scopus, applying bibliographic coupling and co-word analysis to examine the structure, evolution, and thematic development of the field. the bibliographic coupling analysis identifies the current intellectual structure of the research domain, while co-word analysis uncovers its conceptual evolution and emerging research directions. the findings confirm that artificial intelligence is a key driver in transforming education management systems into more intelligent, data-driven, and adaptive frameworks. the study contributes to theoretical development in educational management and socio-technical systems by positioning ai as a central enabler of institutional transformation. this research also provides practical insights for policymakers, educational leaders, and administrators in designing effective ai-based decision support and governance systems to enhance educational performance and institutional sustainability.